Strategic position of the observed enterprise - Todic, Vladimir; Borocki, Jelena; Pervaz, Jovan; Cosic, Ilija (Journal of Production Engineering, 2023)
Strategic planning is the choice of strategy that determines the direction of enterprise development and achieving the set goals. The adopted vision and mission of the realization of the strategic planning process should be based on the possibilities of the company's potential and its focus on both innovation and creative thinking of employees. The analysis of the strategic position of the company and the creation of strategic planning of its development can be done by applying various methods, including SWOT analysis, which is presented in detail in the paper. In the observed company, which deals with Cold and Hot vegetable processing, using SWOT analysis, an assessment of its market position was made and strategic directions in the market were defined, including proposed improvements in strategic planning.